A method to update traditional explanatory dictionaries - Petrauskaitė, Rūta; Dadurkevičius, Virginijus (Taikomoji kalbotyra, 2021)
In the paper the method is presented how to update traditional digitalised dictionaries based on comparison of the dictionary lemmas and a big corpus. Hunspell platform is used for generation of all the word forms from the dictionary lemmas. 6th edition of The Dictionary of Modern Lithuanian was chosen for its comparison with the lexical data from The Joint Corpus of Lithuanian. The outcome of the comparison was two lists of non-overlapping lexis: the list of the dictionary lemmas unused in the present-day Lithuanian and the list of the dictionary gaps, i.e., frequently used words and word forms ignored by the dictionary. The latter is discussed in greater detail to give lexicographers a clue for updates.